The Role of Structural Polymorphism in Driving the Mechanical Performance of the Alzheimer's Beta Amyloid Fibrils - Grasso, Gianvito; Rebella, Martina; Morbiducci, Umberto; Tuszynski, Jack A.; Danani, Andrea; Deriu, Marco A. (Frontiers in Bioengineering and Biotechnology, 2019)
Alzheimer’s Disease (AD) is related with the abnormal aggregation of amyloid β-peptides Aβ1-40 and Aβ1-42, the latter having a polymorphic character which gives rise to U- or S-shaped fibrils. Elucidating the role played by the nanoscale-material architecture on the amyloid fibril stability is a crucial breakthrough to better understand the pathological nature of amyloid structures and to support the rational design of bio-inspired materials. The computational study here presented highlights the superior mechanical behavior of the S-architecture, characterized by a Young’s modulus markedly higher than the U-shaped architecture. The S-architecture showed a higher mechanical resistance to the enforced deformation along the fibril axis, consequence of a better interchain hydrogen bonds’ distribution. In conclusion, this study, focusing the attention on the pivotal multiscale relationship between molecular phenomena and material properties, suggests the S-shaped Aβ1-42 species as a target of election in computational screen/design/optimization of effective aggregation modulators.